Growth of metal-phthalocyanine on GaAs(001): an NEXAFS study - Cabailh, G; McGovern, I; Vearey-Roberts, A; Bushell, A; Evans, D (2005)
Organic semiconductors molecules are often employed as a thin film interlayer to improve electronic and optoelectronic devices. The characterisation of the interface is thus important to understand the physical properties between the organic thin film and the inorganic semiconductor substrate. Also the orientation of the molecules within the film can be of importance. Two molecules, SnPc and MgPc, are studied on argon sputtered GaAs(001)-1×6 using a surface sensitive synchrotron-based technique, Near Edge X-Ray Absorption Fine Structure (NEXAFS). With NEXAFS, the orientation of the molecule is investigated. It is shown that these two molecules have different orientations in thick films, e.g. SnPc lying close to flat to the surface whereas MgPc is 'standing up'. At the monolayer level, however, the SnPc spectra are unchanged, while the MgPc spectra show an orientation reversal. The spectra are discussed with respect to bulk crystalline strucures.